2008
DOI: 10.1007/s10554-008-9328-y
|View full text |Cite
|
Sign up to set email alerts
|

Single Tc99m Sestamibi injection, double acquisition gated SPECT after stress and during low-dose dobutamine infusion: a new suggested protocol for evaluation of myocardial perfusion

Abstract: Our proposed protocol demonstrates good correlation and agreement with standard method and even is superior in some cases especially for estimation of viability after MI. Regarding no need for the rest phase radiotracer injection and imaging, this protocol can be more convenient (except the need for close monitoring of the patient during LDD infusion), less time-consuming, less expensive and moreover with less radiation burden to the patients and personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It has been reported that the MPI-SPECT in cardiac imaging is a widely accepted test for the diagnostic and prognostic evaluation of patients with known, or suspected, CAD [10],[20]. This study indicates that MPI-SPECT may provide more accurate assessments of the extent of CAD, or the prediction of disease outcomes, than CAC alone, given that, in patients with zero CAC, some could demonstrate abnormal myocardial perfusion.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It has been reported that the MPI-SPECT in cardiac imaging is a widely accepted test for the diagnostic and prognostic evaluation of patients with known, or suspected, CAD [10],[20]. This study indicates that MPI-SPECT may provide more accurate assessments of the extent of CAD, or the prediction of disease outcomes, than CAC alone, given that, in patients with zero CAC, some could demonstrate abnormal myocardial perfusion.…”
Section: Discussionmentioning
confidence: 72%
“…Myocardial perfusion imaging (MPI) with gated single photon emission computed tomography (SPECT) has been widely used in the diagnosis of CAD and risk stratification with high diagnostic accuracy[10],[11] when compared to CT angiography. The presence of ischemia could be used to classify the patients as having CAD and candidates for receiving aggressive medical therapy and management.…”
Section: Introductionmentioning
confidence: 99%
“…These images were still plagued with attenuation issues and were reported to be "taken up and retained" within minutes of intravenous injections. Despite the report by DuPont (Crane 1993) and multiple other research and clinical (Everett 1977, Fleming 1992b, 2003e, Aodah 2007, Fallahi 2008) studies discussed above and below, which have clearly established that these isotopes redistribute and do not "stick", most clinicians have continued to ignore Blumgart's teaching of performing sequential evaluations under same state conditions and have subsequently limited their investigation of coronary artery disease to single post-stress imaging despite the teaching of nuclear imaging which notes that "a better indicator of organ function is the change in the activity in a particular organ with time." Newer clinical observations and publications (Sheikine 2010) have since been made confirming our earlier observations from 2000-2001. Inconsistencies in analysis of cardiac imaging have led some researchers (Fleming 2002b, Toriyama 2005, Oregon 2008) to recommend that these clinical studies be standardized quantitatively; something this study has accomplished.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial perfusion imaging (MPI) with stress gated SPECT has been widely used in the diagnosis of CAD and is a well-documented non-invasive method for risk stratification with high diagnostic accuracy when compared to coronary CT angiography [30,31]. The presence of ischemia could be used to classify the patients as having CAD and candidates for receiving aggressive medical therapy and management.…”
Section: Journal Ofmentioning
confidence: 99%